Kinetics of complexation of nickel(II) by DL-isocitric acid - Coronel Canaviri, Edgar (1988)
The kinetics of complexation of Ni¹¹ by isocitric acid have been studied with the stopped-flow method, at 15, 25 and 35°C, ionic strength 0.20 M (NaClO4) and pH range 4.50–6.35. Under our experimental conditions, two processes are observed: the faster reaction takes place within the millisecond time range and the slower one within a few seconds. .A mechanism is proposed to account for the observed behaviour. The rapid process is associated with the complexation itself and the slow one is associated with the deprotonation. For the latter process, the activation energy was determined.